(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, Navoiy’s thoughts on the philosophical teachings of other nations are expressed. Examples of Greek scholars such as Aristotle, Socrates, Bukrat, Jolinus were very important figures for literature. They are found in Navoi’s “ Hamsa “ stories (“Hairat ul-Abror “, “ Farhad and Shirin “, “Saddi Iskandarii” ) and prose works such as “ History of Prophets and Government “. The article focuses on Luqmoni Hakim theonym. Alisher Navoi’s opinions about Lukmani Hakim are analyzed in comparison with the opinions presented in other sources. Scholars’ opinions on the origin of Luqmoni Hakim’s theonym have been studied on the basis of evidence..